An Analysis of Micro Enterprise Development Factors in Dealing Business Competition in Medan City - Siti Mujiatun (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Micro-Enterprise as a business that absorbs the most labor and occupy the third position of the wheels of the economy